The Relationship Between Organizational Culture and Employee Productivity in Private Hospitals in Gorontalo - Nurfitriana, Khansa; Sari, Ayu Kurnia; Reynaldo, Reynaldo (Maroon Journal De Management, 2025)
Organizational culture plays a crucial role in determining employee productivity, especially in the healthcare sector where service quality directly affects patient outcomes. In private hospitals, competitiveness depends on efficiency and patient satisfaction, making cultural alignment with employee performance essential. This study examines the relationship between organizational culture and employee productivity in private hospitals in Gorontalo, Indonesia. Using a quantitative correlational design, data were collected from 150 respondents, including doctors, nurses, and administrative staff across three hospitals, through structured questionnaires assessing teamwork, leadership, communication, innovation, and recognition. Employee productivity indicators included service quality, timeliness, discipline, initiative, and responsiveness. Findings show that most respondents were female (60%) and aged 31–40 years (36.7%), representing the most productive group. Perceptions were strongest in teamwork (70%) and leadership (65.3%), while innovation and recognition were weaker. Productivity was highest in service quality (72%) and responsiveness (70.7%). Correlation analysis showed a strong positive relationship (r = 0.654, p < 0.01), with regression indicating that culture explained 42.8% of productivity variance. Strengthening recognition systems and encouraging innovation can further improve performance and service quality.